Fundamentals of physical acoustics - Blackstock, David T. (John Wiley New York, 2000)
AN AUTHORITATIIVE, UP-TO-DATE INTRODUCTION TO PHYSICAL ACOUSTICS Easy to read and understand, Fundamentals of Physical Acoustics fills a long-standing need for an acoustics text that challenges but does not overpower graduate students in engineering and physics.
Keywords: Sound